DESAIN ANTENA MIKROSTRIP 3.5 GHZ UNTUK APLIKASI 5G MENGGUNAKAN METODE COMPLEMENTARY RHOMBUS RESONATOR UNTUK MENINGKATKAN BANDWIDTH - afifi, muthia; Yulindon, Yulindon; Septima, Uzma (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2024)
In this research, a 3.5 GHz microstrip antenna was designed for 5G applications using the Complemeter Rhombus Resonator method. This antenna has a substrate dimension of 27 mm x 27 mm with a patch length of 23 mm and a patch width of 19.33 mm. The antenna design uses FR4-Epoxy material with a dielectric constant specification of 4.4, a substrate thickness of 1.6 mm, and a copper thickness of 0.035mm. 5G applications require antennas with high performance where this technology is expected to be able to increase data rates and network capacity, which is very capable. Based on the simulation results of microstrip antennas with the Complementary Rhombus Resonator method working at a frequency of 3.5 GHz with a return loss of 26.89 dB. Resulting in the improvement of the antenna bandwidth parameter to 249 MHz, where the bandwidth increases by 20% from the initial design. The initial design has a bandwidth of 208 MHz. This antenna works on the n78 frequency band, where this frequency band has a range of 3300-3800 MHz.